Σχεδίαση και υλοποίηση μηχανισμού διαχείρισης ελαστικής μνήμης σε εικονικά περιβάλλοντα - Τσαλαπάτης, Αιμίλιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2018)
In environments where multiple virtual machines are colocated on the same physical host, the treatment of the guests as ordinary processes by the host leads to the suboptimal distribution of memory between the host and the guests. In this case, solutions such as ballooning, based on working set estimation, are unable to adapt memory distributions fast enough to avoid temporarily starving a guest out of memory[1]. Alternatives such as Transcendent Memory work by being bolted on the guest's swap subsystem, and allowing it to use host memory instead of re- sorting to swapping. All these techniques are applied at the memory management subsystem level, therefore being only indirectly leveraged by applications; this re- sults in cases where the sharp uctuations in memory utilization result in the guest OS being unable to take advantage of them, resulting in unneeded swapping, and even the OOM killer terminating the workload. We propose Userspace Transcen- dent Memory (utmem), a version of Transcendent Memory that can be directly utilized by applications without interference by the OS. Our results demonstrate that such an approach succeeds in allowing the guests to rapidly uctuate their memory usage without the adverse e ects associated with rapid ballooning.